2018
DOI: 10.1016/j.molimm.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

The immunobiology of ubiquitin-dependent B cell receptor functions

Abstract: MHC class II-restricted antigen presentation by dendritic cells is necessary for activation of naïve CD4 T cells, whereas class II-restricted antigen presentation by B lymphocytes and macrophages is important for the recruitment of CD4+ helper and regulatory T cells. Antigen presentation by B cells is also important for induction of T cell tolerance. B cells are unique among these three types of MHC class II-expressing antigen presenting cells (APC) as they constitutively express high levels of cell surface cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 68 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…CD155 surface expression on tumor cells may also be down-regulated by post-translational modifications [57], as previously shown for several immune receptors [58][59][60]. In hepatocellular carcinoma cells, the activation of the unfolded protein response promotes CD155 constitutive degradation and results in a defective NK cell activation against tumor cells [61].…”
Section: Interaction Of Cd155 With Dnam-1 Activating Receptormentioning
confidence: 64%
“…CD155 surface expression on tumor cells may also be down-regulated by post-translational modifications [57], as previously shown for several immune receptors [58][59][60]. In hepatocellular carcinoma cells, the activation of the unfolded protein response promotes CD155 constitutive degradation and results in a defective NK cell activation against tumor cells [61].…”
Section: Interaction Of Cd155 With Dnam-1 Activating Receptormentioning
confidence: 64%
“…Previous work from this laboratory reveals that the Ia. Although M1-and M2-paired conformers of human HLA class II molecules have yet to be immunologically identified, all three isotypes of human class II possess the same GxxxG motif distribution as mouse I-A and I-E molecules (27), and biophysical and in silico studies have shown both M1 and M2 pairing of HLA-DR and HLA-DQ TM domains (13,23,26). Although Ia.2 -M2 MHCII represent ;90% of cell surface I-A k class II molecules (21), Ia.2 + M1 MHCII are enriched in lipid rafts (21) and selectively loaded with peptide derived from the processing of BCR-bound Ags (12).…”
Section: Resultsmentioning
confidence: 97%
“…Although Ia.2 -M2 MHCII represent ;90% of cell surface I-A k class II molecules (21), Ia.2 + M1 MHCII are enriched in lipid rafts (21) and selectively loaded with peptide derived from the processing of BCR-bound Ags (12). Moreover, the 11-5.2 mAb, which selectively binds M1-paired I-A k MHCII (21,22), profoundly blocks both in vitro (21) and in vivo (28) B cell-T cell interactions, indicating a central role for Ia.2 + M1 MHCII in B cell immunobiology (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This depends on whether the BCR resides in the lipid raft and the potential crosslinking of the bound antigen. 61 The B cell antigen presentation process can be summarized into the following three steps: (a) After binding to the Ag, the BCR-antigen complexes are endocytosed and the endocytic vesicle fuses with the endosome (also known as late endosome) containing MHC-II molecules, (b) the formation of MHC-II and digested peptides complex, (c) then the MHC-II-peptide complexes are presented on the cell membrane. [62][63][64] In the first step, the fusion of BCR-Ag-complex targeting to late endosome depends on the ubiquitination of Ig-.…”
Section: Ubiquitination In B Cells Processing Td Antigenmentioning
confidence: 99%